Internet of Things: Low Cost and Wearable SpO2 Device for Health Monitoring - R. R. Adiputra; S. Hadiyoso; Y. Sun Hariyani (Institute of Advanced Engineering and Science, 2018)
This paper discusses a device for measuring oxygen saturation (SpO2) and heart rate as parameters of the representations of heart conditions. SpO2 device that have been made has a small dimension, wearable and high mobility with battery as the main power source. The device connects to a node MCU as a data processor and an internet network gateway to support internet of things applications. Data sent to the Internet cloud can be accessed online and real time via website for further analysis. The error rate at heart rate measurement is ± 2.8 BPM and for oxygen saturation (SpO2) is ± 1.5%. Testing data transmission delay until it can be displayed on website is 3 second that depends on internet traffic conditions.